2018
DOI: 10.1038/s41467-018-05299-x
|View full text |Cite
|
Sign up to set email alerts
|

Gate-controlled quantum dots and superconductivity in planar germanium

Abstract: Superconductors and semiconductors are crucial platforms in the field of quantum computing. They can be combined to hybrids, bringing together physical properties that enable the discovery of new emergent phenomena and provide novel strategies for quantum control. The involved semiconductor materials, however, suffer from disorder, hyperfine interactions or lack of planar technology. Here we realise an approach that overcomes these issues altogether and integrate gate-defined quantum dots and superconductivity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
119
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 42 publications
5
119
2
Order By: Relevance
“…Josephson junctions are defined as a weak link between two superconducting reservoirs, which allows a supercurrent to be transported through intrinsically non-superconducting materials, as long as the junction is shorter than the coherence length [1,2]. While early Josephson junctions realized a weak link by using thin layers of oxide, micro-constrictions, point contacts or grain boundaries [3][4][5][6][7], access to complex mesoscopic semiconducting materials have led to Josephson junctions in which control over the charge carrier density enables in situ tuning of the junction transparency and critical current [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Josephson junctions are defined as a weak link between two superconducting reservoirs, which allows a supercurrent to be transported through intrinsically non-superconducting materials, as long as the junction is shorter than the coherence length [1,2]. While early Josephson junctions realized a weak link by using thin layers of oxide, micro-constrictions, point contacts or grain boundaries [3][4][5][6][7], access to complex mesoscopic semiconducting materials have led to Josephson junctions in which control over the charge carrier density enables in situ tuning of the junction transparency and critical current [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Research on germanium mostly focused on self-assembled nanowires [18][19][20] and demonstrated single-shot spin readout [21] and coherent spin control [15]. However, strained germanium quantum wells were recently shown to support the formation of gate-controlled planar hole quantum dots [22,23]. Now, the crucial challenge is the demonstration of coherent control in this platform and the implementation of qubit-qubit gates for quantum information with holes.Here, we make this step and demonstrate single and two qubit logic with holes in planar germanium.…”
mentioning
confidence: 99%
“…Fabrication is based on silicon substrates and standard manufacturing materials. We grow strained germanium quantum wells, measured to have high hole mobilities µ > 500.000 cm 2 /Vs and a low effective hole mass m h = 0.09 m e [22,24], and predicted to reach m h = 0.05 m e at zero density [25,26]. This allows us to define quantum dots of comparatively large size and we find excellent control over the exchange interaction between the two dots.…”
mentioning
confidence: 99%
“…Therefore, undoped Ge/SiGe quantum wells are preferable for quantum dot fabrication. [11] The transport properties of undoped Ge/SiGe quantum wells are relatively unexplored and effective mass measurements have shown so far conflicting results. In Ref.…”
mentioning
confidence: 99%